Microstructure characteristics induced brittleness of hot isostatic pressing (HIP) diffusion bonded Ni60A hardfacing layer - Lei Yu; Rui Cao; Zhengyi Jiang; Yingjie Yan; Jinyuan Ma; Wanlin Zhao; Lisong Zhu; Fanghui Jia (Journal of Materials Research and Technology)
The fracture behavior of the hot isostatic pressing (HIP) diffusion bonded Ni60A hardfacing layer was evaluated by macro-indentation and uniaxial tensile methods. The macro-indentation fracture toughness (KIC = 15.5 MPa m1/2) and the tensile engineering strain (ԑE = 0.29 %) results show obvious brittleness of the HIP diffusion bonded Ni60A hardfacing layer. Microstructure, nanomechanical properties and fractographic examinations were used to reveal brittleness of the hardfacing layer. On the one hand, the microstructure of the hardfacing layer is comprised of high-volume fractions of brittle silicide, carbide, and boride phases. The volume fraction of plastic nickel-phase regions is merely 22.9 %, and these nickel-phase particles are individually isolated by a matrix of silicide, carbide, and boride phases. The continuous matrix of brittle silicide, carbide, and boride phases results in a low damage tolerance for the hardfacing layer. On the other hand, incoherent phase boundaries of the constituent phases in the hardfacing layer could lead to easy failure along phase boundaries and formation of intergranular cracks.